Splenic Macrophage Subsets and Their Function during Blood-Borne Infections - Borges da Silva, Henrique; Fonseca, Raíssa; Pereira, Rosana Moreira; Cassado, Alexandra dos Anjos; Álvarez, José Maria; D’Império Lima, Maria Regina (Frontiers in Immunology, 2015)
The spleen is one of the major immunological sites for maintaining blood homeostasis. Previous studies showed that heterogeneous splenic macrophage populations contribute in complimentary ways to control blood-borne infections and induce effective immune responses. Marginal metallophilic macrophages (MMMΦs) and marginal zone macrophages (MZMΦs) are cells with great ability to internalize blood-borne pathogens such as virus or bacteria. Their localization adjacent to T and B cell-rich splenic areas favors the rapid contact between these macrophages and cells from adaptive immunity. Indeed, MMMΦs and MZMΦs are considered important bridges between innate and adaptive immunity. Although red pulp macrophages (RpMΦs) are mainly considered scavengers for senescent erythrocytes, several data indicate a role for RpMΦs in control of infections such as blood-stage malaria, as well as in the induction of innate and adaptive immunity. Here, we review current data on how different macrophage subsets recognize and help eliminate blood-borne pathogens, and, in turn, how the inflammatory microenvironment in different phases of infection (acute, chronic and after pathogen clearance) influences macrophage function and survival.